Habitat Selection and Specialisation of Herring Gulls During the Non-breeding Season - O’Hanlon, Nina J.; Thaxter, Chris B.; Burton, Niall H. K.; Grant, Dave; Clark, Nigel A.; Clewley, Gary D.; Conway, Greg J.; Barber, Lee J.; McGill, Rona A. R.; Nager, Ruedi G. (Frontiers in Marine Science, 2022)
Understanding both the distribution and habitat use of populations through the annual cycle is vital to understanding how vulnerable species are to environmental change. However, distributions and habitat use can vary among individuals and populations, particularly in generalist species, with variation depending on external environmental factors, such as resource availability. Comprehensive information across multiple populations is important to guide spatial planning of protected areas and is increasingly available for breeding individuals, but it is still lacking for many species, particularly seabirds, during the non-breeding season, especially those with declining populations. We investigated within-species variation in migratory strategies, non-breeding habitat selection and habitat and spatial specialisation in a declining, opportunistic, generalist seabird, the European herring gull Larus argentatus, from multiple breeding colonies across northwest England and southwest Scotland using global positioning system (GPS) tracking during the non-breeding season of 2014/15. Although several individuals stayed within the area of the breeding colony, the majority of individuals migrated in a southerly direction and spent half of the annual cycle (on average 53%) away from the breeding area and kept moving through the non-breeding period. During non-breeding, herring gulls selected mainly marine intertidal, but also a range of anthropogenic terrestrial habitats. However, habitat selection differed between geographical regions, within a geographical region and among individuals. There was a generalist use of non-breeding habitats at the population level, but some habitat specialisation at the individual level that was repeatable through the non-breeding period despite individuals showing low spatial specialisation. The results highlight the importance of intertidal habitat and a mix of alternative foraging habitats in the wintering areas of herring gulls. The results also highlight that habitat selection in an opportunistic generalist can vary even between nearby regions and that appropriate conservation management plans may need to be tailored to regional differences in specific non-breeding areas.